Strength and Durability Performance of Alkali-Activated Rice Husk Ash Geopolymer Mortar - Yun Yong Kim; Byung-Jae Lee; Velu Saraswathy; Seung-Jun Kwon (The Scientific World Journal)
This paper describes the experimental investigation carried out to develop the geopolymer concrete based on alkali-activated rice husk ash (RHA) by sodium hydroxide with sodium silicate. Effect on method of curing and concentration of NaOH on compressive strength as well as the optimum mix proportion of geopolymer mortar was investigated. It is possible to achieve compressive strengths of 31 N/mm2 and 45 N/mm2, respectively for the 10 M alkali-activated geopolymer mortar after 7 and 28 days of casting when cured for 24 hours at 60°C. Results indicated that the increase in curing period and concentration of alkali activator increased the compressive strength. Durability studies were carried out in acid and sulfate media such as H2SO4, HCl, Na2SO4, and MgSO4 environments and found that geopolymer concrete showed very less weight loss when compared to steam-cured mortar specimens. In addition, fluorescent optical microscopy and X-ray diffraction (XRD) studies have shown the formation of new peaks and enhanced the polymerization reaction which is responsible for strength development and hence RHA has great potential as a substitute for ordinary Portland cement concrete.